Clinical practice guideline for the management of patients with acute lymphoblastic leukemia in Peruvian Social Security (EsSalud) - Rojas Soto, Ninoska (2021)
Introduction: This article summarizes the clinical practice guidelines (CPG) for the management of patients with ALL in the Social Security of Peru (EsSalud). Objective: To provide clinical evidence-based recommendations for the evaluation and management of patients with ALL in EsSalud. Methods: A CPG for the diagnosis and management of patients with ALL in EsSalud was developed. To this end, a guideline development group (local GDG) was established, including medical specialists and methodologists. The local GDG formulated 8 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and -when it was considered pertinent- primary studies were conducted in PubMed and CENTRAL during 2019. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the local GDG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice, and flowcharts of evaluation and management. Lastly, the CPG was approved with Resolution N° 23-DGPCFyT–IETSI-ESSALUD-2019. Results: This CPG addressed 8 clinical questions, divided into four topics: diagnosis, general measures, pharmacological management, and surgical management of ALL. Based on these questions, 5 recommendations (3 strong recommendations and 2 weak recommendations), 20 points of good clinical practice, and 3 flowcharts were formulated. Conclusion: This article summarizes the methodology and evidence-based conclusions from the CPG for the diagnosis and management of ALL in EsSalud.